Potential Usefulness of Streptococcus pneumoniae Extracellular Membrane Vesicles as Antibacterial Vaccines - Chi-Won Choi; Edmond Changkyun Park; Sung Ho Yun; Sang-Yeop Lee; Seung Il Kim; Gun-Hwa Kim (Journal of Immunology Research)
The secretion of extracellular membrane vesicles (EMVs) is a common phenomenon that occurs in archaea, bacteria, and mammalian cells. The EMVs of bacteria play important roles in their virulence, biogenesis mechanisms, and host cell interactions. Bacterial EMVs have recently become the focus of attention because of their potential as highly effective vaccines that cause few side effects. Here, we isolated the EMVs of Streptococcus pneumoniae and examined their potential as new vaccine candidates. Although the S. pneumoniae bacteria were highly pathogenic in a mouse model, the EMVs purified from these bacteria showed low pathological activity both in cell culture and in mice. When mice were injected intraperitoneally with S. pneumoniae EMVs and then challenged, they were protected from both the homologous strain and another pathogenic serotype of S. pneumoniae. We also identified a number of proteins that may have immunogenic activity and may be responsible for the immune responses by the hosts. These results suggest that S. pneumoniae EMVs or their individual immunogenic antigens may be useful as new vaccine agents.